(untitled) (Estudos em Design, 2015)
This article presents the Cartesian modeling technique applied to the construction of costumes to the dancers from APAE Jaraguá do Sul. The users from this group have different degrees of disabilities and body biotypes with anatomical variations that must be analyzed individually in order to create opportunities for them to develop dance costumes that encourage autonomy. The focus of the development of these pieces is the adequacy of the product to the dancers’ anatomy in order to improve their performance, paying attention to safety, aesthetic and emotional comfort, ease of handling and usability.